Gelcasting of alumina via cross-linking of a polyelectrolyte dispersant. Issue 6 (15th April 2020) - Lu, Yuju; Gan, Ke; Liu, Jingjing; Ren, Bo; Zhang, Xiaoyan; Rong, Yedong; Xu, Jie; Yang, JinLong
Abstract: A new gelcasting approach of alumina inspired by Isobam was designed utilizing a polyelectrolyte dispersant named BTT, which is able to form cross-links via thiol-ene reaction with pentaerythritol tetrakis(2-mercaptoacetate). Measurement of zeta potential and viscosity shows good dispersion ability of BTT in 52 vol% alumina suspensions. The flow curves and shear modulus of wet green bodies during gelation demonstrate its high gelation strength in comparison with Isobam. The analysis of effects of addition of ammonium citrate tribasic into the system indicates that a polymer-particle double network is supposed to form during gelation. Elastic part and viscous part of gelation strength of the system are mainly dominated by interaction between polyelectrolyte and particles and cross-linking respectively, which accounts for the existence of both high gelation strength and flexibility of wet green bodies fabricated in this approach.